Comparison of the hydraulic response of Pinus taeda L. and hybrid pine PEE×PCH INTA-PINDO under water deficit and rehydration - Schoffen, Cristian Damián; Bulfe, Nardia María (Sociedad Argentina de Fisiología Vegetal (SAFV), 2025)
Póster y resúmen